"WE FEEL ANXIOUS AND NERVOUS": THE UNDERGRADUATE ENGLISH STUDENTS' EMOTIONAL EXPERIENCES IN LEARNING TO SPEAK ENGLISH - Diyah Nurmasadah; Supiani Supiani; Angga Taufan Dayu (JURNAL EDUSCIENCE (JES), 2022)
The purpose of this research was to explore the undergraduate English students’ emotional experience in terms of anxious and nervous feelings and identify the factors contributing to the anxious and nervous feelings of undergraduate English students in learning to speak English. The design of this research employs qualitative narrative approach, in which the researchers attempts to elicit the participants’ emotional experience in learning speaking at the private university in Banjarmasin. In collecting the data, the researchers use semi-structured interview techniques and are analyzed using thematic inductive approach. From the findings revealed that there were three undergraduate students who experienced dominant negative emotions such as anxiety, nervous and shy during learning to speak English, while another student considered that negative emotions did not influence him too much to speak English. There were two main factors that contributing anxiety and nervousness, namely external factors (such as lack of confidence and the environment) and internal factors (such as lacking mastery of grammar and vocabulary).Keywords: Emotional experinces, learning to speak English, undergraduate students